Perceived Meaning and Common Errors in Google Translate's Translation of Goodreads Reviews - Amanda Jessie Fatrisya (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
The study analyzes translation on meaning. It aims to examine the extent to which Google Translate can preserve meaning and find the most common errors created by Google Translate when translating English customer reviews into Bahasa Indonesia from fiction books on the Goodreads website. Further, when analyzing the data, the writer used Bowker (2023) theory of translation on meaning and a qualitative approach. The study shows that some data were error-free, and some revealed that translation errors were found, where Google Translate chose a slightly incorrect choice of vocabulary and a wrong choice of vocabulary, leading to an error in meaning. In addition, other errors were classified into two categories: vocabulary errors and translation technique errors. Moreover, the study reveals that the most common errors were failing to translate idiomatic expressions. The study concludes that the data showed more errors than error-free.